The Influence of Marketing Mix Factors in Purchasing Decision for Wooden Furniture Case of Furnimart Bogor - Parmana Parmana; Idqan Fahmi; Dodik Ridho Nurrohmat (School of Business, IPB University (SB-IPB), 2019)
The objectives of this research were to analyze consumer’s perception of marketing mix, to analyze the effects of marketing mix towards purchase decision, and to formulate strategies to increase consumer purchases at Furnimart Bogor. The data retrieval technique was conducted using in-depth interviews to key persons in Furnimart, consumers and obtaining data from the previous research. There were 13 variables used in this study with 120 samples chosen at random. The data were processed using descriptive analysis and Structural Equation Modelling (SEM), through LISREL 8.72. The results of the research showed that consumer perception on the marketing mix consisting of product, price, place and promotion stated that 75.83% of consumers rated the product design as good, 60.5%t competitive price, and 75.63% said that Furnimart store location was easy to reach and offered attractive promotion. The results of SEM analysis showed that the most influencing components of the marketing mix towards the consumer’s purchasing decisions of furniture products were price and promotion.Keywords: furniture, marketing mix, perception, purchasing decision, SEM